A synthesis method for Pt single atoms and clusters loaded inside nitrogen-doped porous carbon

By growing Pt nanoparticles in situ in UiO-66-NH2 and sintering at high temperature, nitrogen-doped porous carbon materials with single atoms and clusters were prepared, which solved the problem of insufficient activity and stability of single atom catalysts under high current density, and achieved efficient electrocatalytic hydrogen evolution performance and good cycling stability.

CN116043269BActive Publication Date: 2025-03-14UNIV OF SHANGHAI FOR SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310127408.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-17
Publication Date
2025-03-14
Estimated Expiration
2043-02-17

AI Technical Summary

Technical Problem

In the prior art, the low metal loading and thermodynamic instability of single atom catalysts limit their activity and stability of electrocatalytic hydrogen evolution at high current density.

Method used

By growing Pt nanoparticles in situ in UiO-66-NH2 and sintering at high temperature, nitrogen-doped porous carbon materials with single atoms and clusters were prepared, which improved the stability of the catalyst and electrocatalytic hydrogen evolution activity.

Benefits of technology

It effectively improves the utilization rate of platinum metal active sites, optimizes the hydrogen evolution activity of the material under alkaline and neutral conditions, and improves the electrocatalytic cycle stability, reducing the cost of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116043269B_ABST
    Figure CN116043269B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for synthesizing Pt single atoms and clusters loaded inside nitrogen-doped porous carbon, comprising: S1, obtaining Pt nanoparticles by a chemical solution method; S2, synthesizing Pt / UiO-66-NH2 by in-situ growth using a solvent thermal method; S3, sintering Pt / UiO-66-NH2 at a high temperature to obtain Pt SA ‑Pt C / NDPCM. According to the present invention, by in-situ growing Pt nanoparticles inside UiO‑66‑NH2 and performing high-temperature sintering, a nitrogen-doped porous carbon material with single-atom and cluster loading is obtained, and the electrocatalytic hydrogen production is promoted, while its stability is improved, and the cost of the catalyst is further reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hydrogen production by electrolysis of water, and in particular to a synthesis method of Pt single atoms and clusters loaded inside nitrogen-doped porous carbon. Background Art

[0002] Hydrogen production by water electrolysis is one of the effective ways to solve the current energy crisis. Platinum (Pt) is currently the best catalyst for hydrogen production by water electrolysis, but the scarcity of precious metal Pt resources and high cost have severely limited its widespread application. Single atom catalysts (SACs) are catalysts with only isolated single atoms dispersed on the surface of the carrier. They have the advantages of maximum atomic utilization efficiency, high selectivity and high catalytic activity. Reducing the size of Pt nanoparticles to the size of clusters or even single atoms can significantly reduce the amount of precious metals used and improve their catalytic activity. However, due to the small size of single atoms, thermodynamically unstable isolated atoms are easily aggregated due to high surface free energy. Therefore, in most cases, SACs have a low metal loading of less than 1wt%, which reduces their overall catalytic activity and especially limits their industrial application at high current density.

[0003] In the related art, the morphology of the catalyst material prepared by the high-temperature sintering method is difficult to control, so that the stability of the material in the electrocatalytic hydrogen evolution process is not significantly improved, and its inherent defects are not substantially compensated, so that its hydrogen evolution kinetics are not significantly improved. Since the single-atom catalyst is easy to agglomerate and the metal site loading is low, its electrocatalytic hydrogen evolution activity is poor, and it is impossible to stably evolve hydrogen at a higher current density. Summary of the invention

[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for synthesizing Pt single atoms and clusters loaded in nitrogen-doped porous carbon. By in-situ growing Pt nanoparticles inside UiO-66-NH2 and sintering at high temperature, a nitrogen-doped porous carbon material loaded with single atoms and clusters is obtained, and electrocatalytic hydrogen production is promoted, while improving its stability and further reducing the cost of the catalyst. In order to achieve the above-mentioned purpose and other advantages according to the present invention, a method for synthesizing Pt single atoms and clusters loaded in nitrogen-doped porous carbon is provided, comprising:

[0005] S1, obtaining Pt nanoparticles by a chemical solution method;

[0006] S2, synthesizing Pt / UiO-66-NH2 by in situ growth using a solvothermal method;

[0007] S3, sinter Pt / UiO-66-NH2 at high temperature to obtain Pt SA -Pt C / NDPCM.

[0008] Preferably, step S1 further comprises the following steps:

[0009] S11, dissolving chloroplatinic acid hexahydrate powder in deionized water to obtain a uniform solution A;

[0010] S12, adding methanol to polyvinyl pyrrolidone powder, recorded as solution B;

[0011] S13, uniformly mixing solution A and solution B, and heating them under a nitrogen atmosphere for 3 hours, and removing excess solvent by rotary evaporation;

[0012] S14. The product was collected by washing with anhydrous acetone and chloroform three times respectively, and after drying, the product was evenly dispersed in N,N-dimethylformamide.

[0013] Preferably, step S2 further comprises the following steps:

[0014] S21, placing the Pt nanoparticles, zirconium chloride, 2-aminoterephthalic acid, glacial acetic acid and N,N-dimethylformamide in a reaction kettle;

[0015] S22. After reacting under ultrasonic and high temperature conditions, the mixture is cooled to room temperature, washed three times with N,N-dimethylformamide and ethanol, and dried to obtain the product.

[0016] Preferably, step S3 further comprises the following steps:

[0017] S31, placing Pt / UiO-66-NH2 in a tube furnace;

[0018] S32. In a H2 / Ar atmosphere, the temperature was increased at a rate of 2°C / min and the product was obtained after calcination for 2 hours.

[0019] Preferably, in step S2, ultrasonic treatment is performed for 10 minutes, the reactor is placed in an oven and reacted at 120° C. for 24 hours, cooled to room temperature, washed three times with N,N-dimethylformamide and ethanol, and vacuum dried at 60° C. for 8 hours to obtain Pt / UiO-66-NH2.

[0020] Preferably, in step S3, the temperature is raised to 900°C in a H2 / Ar atmosphere at a rate of 2°C / min and calcined for 2 hours to obtain Pt SA -Pt C / NDPCM.

[0021] Compared with the prior art, the present invention has the following beneficial effects: effectively improving the utilization rate of platinum metal active sites, greatly optimizing the hydrogen evolution activity of the material under alkaline and neutral conditions, and having good electrocatalytic cycle stability. The above characteristics make the prepared electrocatalyst have more excellent electrocatalytic hydrogen evolution performance than commercial Pt / C. It improves the situation that single atoms are easy to agglomerate, achieves a larger current density under alkaline and neutral conditions, and can maintain cyclic hydrogen production activity. Due to the presence of single atoms and clusters, the effective utilization rate of Pt is improved, the inherent catalytic performance is improved, and the long-term cycle stability of the material is optimized through the externally wrapped nitrogen-doped porous carbon skeleton. The material has the characteristics of simple process, easy availability of raw materials, and simple preparation process. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 A flow chart of the preparation of the synthesis method of Pt single atoms and clusters loaded inside nitrogen-doped porous carbon according to the present invention;

[0023] Figure 2 A morphology diagram of a synthetic material obtained by the synthesis method of the present invention in which Pt single atoms and clusters are loaded inside nitrogen-doped porous carbon;

[0024] Figure 3 An X-ray diffraction diagram of Pt single atoms and clusters loaded inside nitrogen-doped porous carbon according to the present invention;

[0025] Figure 4 The isothermal adsorption-desorption curve of nitrogen of Pt single atoms and clusters loaded inside nitrogen-doped porous carbon according to the present invention;

[0026] Figure 5 The electrocatalytic hydrogen evolution performance diagram of Pt single atoms and clusters loaded inside nitrogen-doped porous carbon according to the present invention;

[0027] Figure 6 The Pt single atoms and clusters according to the present invention are loaded on the Pt inside the nitrogen-doped porous carbon. SA -Pt C / Graph of the cyclic activity of NDPCM under alkaline conditions. DETAILED DESCRIPTION

[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] Reference Figure 1-6A method for synthesizing Pt single atoms and clusters loaded inside nitrogen-doped porous carbon comprises the following steps: 1. Synthesis of Pt nanoparticles

[0030] Take a certain amount of chloroplatinic acid hexahydrate powder and dissolve it in deionized water to obtain a uniform solution A. Take a certain amount of polyvinyl pyrrolidone powder and add methanol, which is recorded as solution B. Evenly mix solution A and solution B, heat them under a nitrogen atmosphere for 3 hours, and remove excess solvent by rotary evaporation. Then wash the product three times with anhydrous acetone and chloroform respectively, collect it, and evenly disperse the product in N,N-dimethylformamide after drying.

[0031] 2. Synthesis of Pt / UiO-66-NH2

[0032] A certain amount of the prepared Pt nanoparticles, zirconium chloride, 2-aminoterephthalic acid, glacial acetic acid and N,N-dimethylformamide were taken out and placed in a reaction kettle and ultrasonicated, reacted at 120°C for 24 hours, cooled to room temperature, washed three times with N,N-dimethylformamide and ethanol, and dried to obtain the product.

[0033] 3.Pt SA -Pt C Synthesis of NDPCM

[0034] Pt / UiO-66-NH2 was placed in a tube furnace and heated to a certain temperature at a heating rate of 2°C / min in a H2 / Ar atmosphere, and the product was obtained after calcination for 2 hours.

[0035] Specific implementation method 1: This implementation method provides a method for synthesizing Pt single atoms and clusters loaded on nitrogen-doped porous carbon internal materials according to the following steps:

[0036] 1. Synthesis of Pt Nanoparticles

[0037] Take 62.15 mg of chloroplatinic acid hexahydrate powder and dissolve it in 20 mL of deionized water to obtain a uniform solution A. Take 88.3 mg of polyvinyl pyrrolidone powder and add 60 mL of methanol, which is recorded as solution B. Evenly mix solution A and solution B, heat to 73 ° C under a nitrogen atmosphere for 3 hours. Remove excess solvent by rotary evaporation. Then wash the product three times with anhydrous acetone and chloroform respectively, collect it, and after drying, evenly disperse the obtained powder in N, N-dimethylformamide to obtain Pt nanoparticles.

[0038] 2. Synthesis of Pt / UiO-66-NH2

[0039] 93.2 mg of zirconium chloride, 72.4 mg of 2-aminoterephthalic acid and 40 mL of N,N-dimethylformamide were placed in a reactor and ultrasonicated for 5 minutes. 4.2 mg of the Pt nanoparticles prepared above and 2.74 mL of glacial acetic acid were added and ultrasonicated for 10 minutes. The reactor was placed in an oven and reacted at 120°C for 24 hours. After cooling to room temperature, it was washed three times with N,N-dimethylformamide and ethanol, and vacuum dried at 60°C for 8 hours to obtain Pt / UiO-66-NH2.

[0040] 3. Pt SA -Pt C Synthesis of NDPCM

[0041] The Pt / UiO-66-NH2 prepared in the previous step was placed in a tube furnace and heated to 900°C at a rate of 2°C / min in a H2 / Ar atmosphere. After calcination for 2 hours, Pt SA -Pt C / NDPCM.

[0042] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that the amount of Pt nanoparticles added in step 2, 4.2 mg, can be changed.

[0043] Specific implementation method three: This implementation method is different from specific implementation method one in that the sintering temperature of 900° C. in step three can be changed.

[0044] The present invention uses MOFs materials as single-atom carriers, effectively suppresses the agglomeration of single atoms, and prevents the electrolyte from corroding the active sites of the catalyst during the electrocatalytic electrolysis of water, effectively improving the cycle stability of the electrocatalyst. By regulating the temperature of high-temperature annealing, the prepared nitrogen-doped porous carbon material has single atoms and clusters in different proportions, and the raw materials for preparation are easy to obtain, and the preparation is prepared by a solvent thermal method and a high-temperature sintering method, the process is simple, and the catalyst has excellent electrocatalytic hydrogen evolution performance under alkaline and neutral conditions relative to commercial Pt / C catalysts, a smaller overpotential, a smaller Tafel slope, a greater mass activity, and good material stability. At the same time, it also has the advantage of low price, which is conducive to further promotion and application.

[0045] This embodiment enables single atoms and clusters to be successfully loaded inside nitrogen-doped porous carbon. The present invention effectively improves the utilization rate of platinum metal active sites, greatly optimizes the hydrogen evolution activity of the material under alkaline and neutral conditions, and has good electrocatalytic cycle stability. The above characteristics make the prepared electrocatalyst have better electrocatalytic hydrogen evolution performance than commercial Pt / C.

[0046] The present invention synthesizes a material in which Pt single atoms and clusters with unique structures are loaded inside nitrogen-doped porous carbon, and by regulating the temperature of high-temperature sintering and the loading amount of Pt, a catalyst for hydrogen evolution by electrolysis of water with superior performance is obtained. Among them, the simultaneous presence of single atoms and clusters effectively improves the utilization rate of metal active sites, greatly optimizes the hydrogen evolution activity of the material under alkaline and neutral conditions, and overcomes the defect of poor hydrogen production activity under high current density. In addition, due to the structure of external nitrogen-doped porous carbon, the material also has good electrocatalytic cycle stability.

[0047] The present invention provides a method for preparing Pt single atoms and clusters loaded inside octahedral nitrogen-doped porous carbon, and the prepared electrocatalytic material is suitable for electrolyzing water to produce hydrogen under alkaline conditions and neutral conditions. In addition, due to the composite of single atoms and clusters, the effective utilization rate of Pt is increased, the inherent catalytic performance of the catalyst is improved, and the long-term cycle stability of the material is optimized by the nitrogen-doped porous carbon skeleton wrapped externally. The material has the characteristics of simple process, easy availability of raw materials, and simple preparation process, and has very important practical significance.

[0048] in Figure 2 The results show that the synthesized UiO-66-NH2 has a regular octahedral structure, in which platinum particles are uniformly added to the core of UiO-66-NH2. After sintering at 900℃, the morphology of UiO-66-NH2 remains basically unchanged, and Pt is mainly dispersed on the carrier in the form of single atoms and clusters.

[0049] Figure 3 The successful synthesis of UiO-66-NH2 and Pt / UiO-66-NH2 is shown in Figure 2. SA -Pt C The main diffraction peak of / NDPCM can correspond to the Pt peak of the standard card, proving that Pt SA -Pt C / Successful synthesis of NDPCM.

[0050] Figure 4 UiO-66-NH2, Pt / UiO-66-NH2, NDPCM and Pt SA -Pt C The BET surface areas of / NDPCM are 275.88, 212.84, 204.00 and 250.28 m 2 g -1 These samples show typical type IV mesoporous characteristic isotherms, and the materials are mainly composed of mesopores ranging from 6 to 12 nm.

[0051] Figure 5 The optimal ratio Pt shown SA -Pt C / NDPCM (the amount of added Pt nanoparticles was 4.2 mg, and the high-temperature sintering temperature was 900°C) showed improved catalytic performance compared to other comparative catalysts and commercial 10% Pt / C, with a small overpotential and Tafel slope under alkaline and neutral conditions. The Pt content was 2.39wt% as determined by ICP element content testing.

[0052] Figure 6 It is shown that after up to 10,000 cycles of CV cycle stability testing, the catalyst can still maintain its original catalytic activity with negligible attenuation.

[0053] The number of devices and processing scales described here are used to simplify the description of the present invention, and the application, modification and variation of the present invention will be obvious to those skilled in the art.

[0054] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the illustrations shown and described herein.

Claims

1. A method for synthesizing Pt single atoms and clusters loaded inside nitrogen-doped porous carbon, characterized in that: The following steps are involved: S1, obtaining Pt nanoparticles by a chemical solution method; S2, using a solvothermal method to perform in-situ growth synthesis of Pt / UiO-66-NH2; specifically comprising the following steps: S21, placing the Pt nanoparticles, zirconium chloride, 2-aminoterephthalic acid, glacial acetic acid and N,N-dimethylformamide in a reaction kettle; S22, placing the reactor in an oven at 120° C. for 24 hours, cooling to room temperature, washing with N,N-dimethylformamide and ethanol three times, and drying to obtain Pt / UiO-66-NH2; S3, sinter Pt / UiO-66-NH2 at high temperature to obtain Pt SA -Pt C / NDPCM, wherein the Pt SA -Pt C / NDPCM.

2. The method for synthesizing Pt single atoms and clusters loaded inside nitrogen-doped porous carbon according to claim 1, characterized in that: Step S1 also includes the following steps: S11, dissolving chloroplatinic acid hexahydrate powder in deionized water to obtain a uniform solution A; S12, adding methanol to polyvinyl pyrrolidone powder, recorded as solution B; S13, uniformly mixing solution A and solution B, and heating them under a nitrogen atmosphere for 3 hours, and removing excess solvent by rotary evaporation; S14. The product was collected by washing with anhydrous acetone and chloroform three times respectively, and after drying, the product was evenly dispersed in N,N-dimethylformamide.

3. The method for synthesizing Pt single atoms and clusters loaded inside nitrogen-doped porous carbon according to claim 1, characterized in that: Step S3 also includes the following steps: S31. Place Pt / UiO-66-NH2 in a tube furnace for high-temperature sintering.

4. The method for synthesizing Pt single atoms and clusters loaded inside nitrogen-doped porous carbon according to claim 1, characterized in that: In step S2, ultrasonic treatment was performed for 10 minutes and vacuum drying was performed at 60° C. for 8 hours to obtain Pt / UiO-66-NH2.

Citation Information

Patent Citations

  • Synthesis and application of Pt atomic cluster synergistic Pt monatomic electrocatalytic material

    CN116657175A